Kajian Penggunaan Antibiotik pada Pasien Sepsis dengan Gangguan Ginjal - Hidayati Hidayati; Helmi Arifin; Raveinal Raveinal (Fakultas Farmasi Universitas Andalas, 2016)
Prospective observational study was conducted to investigate antibiotic using, by evaluating clinical pharmacokinetic and antibiotic quality on septic patient with kidney disorder in Interne Department at Hospital X. Septic patients with kidney disorder treated with antibiotic for 4 months. The evaluated antibiotic are excreted by kidney mainly. The clinical aspects of evaluation are kinds of antibiotic, dosage, frequency, period of treatment, and clinical drug interaction. The evaluation of antibiotic quality used Gyssens method. Total respondens were 40 patients, treated with 8 kinds of antibiotic. Among 8 of them, there were 5 antibiotic which were excreted mainly by kidney. From five antibiotics, it was found that the accurate dosage adjustment on 29 patients (74,3%), and unproperly adjustment in 10 patients (10,25%) that adjust upper individual dosage that calculate pharmacokinetically. There were five interactions that clinically significant. The evaluation of antibiotic using qualitatively by Gyssens method found that 4 patients (10%) as incomplete therapy/VI category, two patients (5%) were ineffective category IVa, 1 patient (2,5%) as unsafe category IVb, 9 patients (22,5%) as inappropriate dosage adjustment, and 23 patients (57,5%) as appropriate antibiotic category 0. Conclusion: Using antibiotic that mainly excreted by kidney in septic patients with kidney disorder, generally doesn’t show bad impact in kidney of patient.